Neutrophil-lymphocyte ratio as a predictor of recurrence and progression in patients with high-grade pT1 bladder cancer - Özyalvaçlı, Mehmet Emin; Ozyalvacli, Gulzade; Kocaaslan, Ramazan; Cecen, Kursat; Uyeturk, Ugur; Kemahli, Eray; Gucuk, Adnan (Canadian Urological Association Journal, 2015)
Introduction: We investigated the value of the preoperative neutrophil- lymphocyte ratio (NLR) in predicting recurrence and progression of high-grade pT1 non-muscle-invasive tumour in patients with bladder cancer during a 5-year follow-up period. Methods: We retrospectively reviewed data of 1100 patients with bladder cancer; these patients underwent transurethral resection and were monitored at multiple centres from 2008 to 2013. In total, 166 consecutive and newly diagnosed patients with highgrade pT1 tumours were included in this study. The NLR was calculated by dividing the absolute neutrophil count by the absolute lymphocyte count. Results: Of the 166 patients, 152 were male. The patients were evaluated as two separate groups in terms of recurrence and progression. The mean follow-up period was 24.2 months (interquartile range 13.8–36.6 months). A statistically significant difference was found between recurrence and tumour size (p = 0.001), number of tumours (p < 0.001), NLR (p < 0.001), and smoking (p = 0.007). No statistically significant correlation was found between NLR and progression. According to receiver operating characteristic (ROC) analysis, the optimum cut-off value for the NLR was ≥2.43 (74% sensitivity, 60% specificity, p < 0.001; area under the curve [AUC] 0.687, 95% confidence interval [CI] 0.607–0.767). Multivariate logistic regression analysis determined that the following factors were independent predictors of recurrence in patients with high-grade pT1 non-muscle-invasive bladder cancer: tumour number (OR 5.32, 95% CI 2.10–12.90), NLR of ≥2.43 (OR 2.587; 95% CI 1.156–5.789), and smoking (OR 4.17, 95% CI 1.31–13.21). Conclusion: A high preoperative NLR may play an important role in predicting recurrence of superficial transitional cell type highgrade pT1 bladder tumours. Prospective studies are required to validate the role of NLR as a prognostic marker in high-grade pT1 bladder tumours.